General population normative values for the EORTC QLQ-C30 by age, sex, and health condition for the French general population - Micha J. Pilz; Fanny L.C. Loth; Sandra Nolte; Anna M.M. Thurner; Eva-Maria Gamper; Amélie Anota; Gregor Liegl; Johannes M. Giesinger; on behalf of the EORTC Quality of Life Group (SpringerOpen, 2024)
Abstract Background General population normative values for the widely used health-related quality of life (HRQoL) measure EORTC QLQ-C30 support the interpretation of trial results and HRQoL of patients in clinical practice. Here, we provide sex-, age- and health condition-specific normative values for the EORTC QLQ-C30 in the French general population. Methods French general population data was collected in an international EORTC project. Online panels with quota samples were used to recruit sex and age groups. Number and type of comorbidities were assessed. Descriptive statistics were used to calculate general population values for each QLQ-C30 scale, separately for sex, age, and presence of one- and more chronic health conditions. A multivariate linear regression model has been developed to allow estimating the effect of sex, age, and the presence for one- and more chronic health conditions on EORTC QLQ-C30 scores. Data was weighted according to United Nation statistics adjusting for the proportion of sex and age groups. Results In total, 1001 French respondents were included in our analyses. The weighted mean age was 47.9 years, 514 (51.3%) participants were women, and 497 (52.2%) participants reported at least one health condition. Men reported statistically significant better scores for Emotional Functioning (+9.6 points, p = 0.006) and Fatigue (−7.8 point; p = 0.04); women reported better profiles for Role Functioning (+8.7 points; p = 0.008) and Financial Difficulty (−7.8 points, p = 0.011). According to the regression model, the sex effect was statistically significant in eight scales; the effect of increasing age had a statistically significant effect on seven of the 15 EORTC QLQ-C30 scales. The sex- and age effect varied in its direction across the various scales. The presence of health conditions showed a strong negative effect on all scales. Conclusion This is the first publication of detailed French normative values for the EORTC QLQ-C30. It aims to support the interpretation of HRQoL profiles in French cancer populations. The strong impact of health conditions on QLQ-C30 scores highlights the importance of considering the impact of comorbidities in cancer patients when interpreting HRQoL data.